2018
DOI: 10.1038/s41598-018-32735-1
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake-induced structural deformations enhance long-term solute fluxes from active volcanic systems

Abstract: Evidence for relationships between seismotectonic activity and dissolved weathering fluxes remains limited. Motivated by the occurrence of new springs emerging after the 2016 Kumamoto earthquake and supported by historical groundwater data, this study focuses on the long-term effect of near-surface structural deformation on the contribution of deep, highly saline fluids to the solute fluxes from the Aso caldera, Kyushu, Japan. Available hydrologic and structural data suggest that concentrated, over-pressured g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 82 publications
(106 reference statements)
2
25
0
Order By: Relevance
“…For instance, analysis of a long-term chemical monitoring dataset revealed post-seismic NO 3 − increase in groundwaters in recharge areas that is attributed to enhanced percolation of soil porewaters into aquifers from agricultural fields triggered by seismic vibrations 38 . The same study also revealed a post-seismic increase in the contribution of deep fluids to surface aquifers based on geochemical tracers, in particular Cl − , SO 4 2− , and B, as has been documented in many other instances [41][42][43][44][45][46] . This phenomenon occurs near the epicentre of earthquakes and in geothermal regions 38 .…”
Section: Recharge Areasupporting
confidence: 64%
“…For instance, analysis of a long-term chemical monitoring dataset revealed post-seismic NO 3 − increase in groundwaters in recharge areas that is attributed to enhanced percolation of soil porewaters into aquifers from agricultural fields triggered by seismic vibrations 38 . The same study also revealed a post-seismic increase in the contribution of deep fluids to surface aquifers based on geochemical tracers, in particular Cl − , SO 4 2− , and B, as has been documented in many other instances [41][42][43][44][45][46] . This phenomenon occurs near the epicentre of earthquakes and in geothermal regions 38 .…”
Section: Recharge Areasupporting
confidence: 64%
“…While there are rivers in the area, groundwater is the preferred water source due to the high permeability in the study area, groundwater's seasonal stability (against drought, etc. ), groundwater's superior water quality (Hosono et al, 2018), and the prohibitive infrastructure costs associated with capturing surface water. In this study, we focus on the potential benefits and costs of the water ponding subsidy program.…”
Section: History Of Groundwater In Kumamoto Citymentioning
confidence: 99%
“…Recharge was estimated assuming that 100 mm of river water is applied daily for 30-90 days per year over the total paddy field area, which translates to an effective recharge rate of 3-9 m 3 per year for every 1 m 2 of paddy field area watered. Note that the sudden drop in all subsidy program-related indicators (number of farmers, subsidy level, watered area, and recharge gain) in Figure 3 are due to the Kumamoto inland earthquakes which started by a large foreshock of M w 6.2 on April 14 2016, followed by the main shock of M w 7.0 the next day (e.g., Hosono et al, 2018). These earthquakes caused serious damage to infrastructures and surface-and subsurface lands including agricultural farm land and its irrigation system.…”
Section: History Of the Kumamoto Water Ponding Subsidy Programmentioning
confidence: 99%
“…Discharge of these fluids is commonly observed in vicinity of active volcano-hydrothermal fields. For example, relevant number of studies tried to depict origins and pathways of deep originated fluids to quantify the impact of volcanic and magmatic activities on lateral material transportations from land to ocean (Chiodini et al 2000;Dessert et al 2009;Gaillardet et al 2011;Rive et al 2013;Hosono et al 2018;Perez-Fodich and Derry 2019). Similar high concentration hot spring waters are found in regions where active volcanic and magmatic activities are not existing (Tomaru et al 2007;Kusuda et al 2014;Togo et al 2014;Morikawa et al 2016;Kusuhara et al 2020 and references therein), however, origin, distribution, pathway, and thus their impact of hydrochemical features on surface systems are less well known.…”
Section: Introductionmentioning
confidence: 99%
“…Stable carbon isotope ratio of dissolved inorganic carbon (δ 13 C) is a fundamental tracer for identifying a contribution of magmatic or mantle-derived carbon in fluids (e.g., Chiodini et al 2000;Yamada et al 2011;Rive et al 2013). Sulfur isotope ratio of dissolved sulfate (δ 34 S) is also applicable for evaluating volcanic influence on spring waters and for interpreting redox processes in aquifer environments (e.g., Kusakabe et al 2000;Hosono et al 2014aHosono et al , 2018. This study integrates the results from these isotopic analyses and characterized geochemical features of hot spring waters with comparison of those from other surface waters for trying to find out the signature of deep crustal fluid upwelling and to assess its impact on surface hydrological systems.…”
Section: Introductionmentioning
confidence: 99%